Political and Social Participation of Afghan Women Post-2001 - NUSRAT, FATEMA (İstanbul Kültür Üniversitesi, 2022)
Women in Afghanistan lived a life full of ups and downs throughout history. Despite their strengths and capabilities, they have always been the victims of cultural and traditional restrictions and conservatism. But when they were given a chance, they played extraordinary roles in different stages of life and proved to be as capable as men when it came to socio-political development. This study investigates the position of Afghan women throughout the twentieth century and in post-2001. It describes the supports provided and reforms initiated by different governments to empower women and enhance their participation in the power structure. At the same time, it highlights the challenges resulting from conservativism and extremism that hindered women's empowerment in Afghanistan and restricted them from practicing their rights and freedoms. The primary objective of this thesis is to reveal the improving conditions of Afghan women after 2001 as a result of supports provided by the international community and reforms initiated by the governments. Meanwhile, it evaluates women's political and socio-economic participation after 2001. It also analyzes the external and internal factors that led to women's empowerment and enhanced their participation in the power structure. This study mainly uses secondary data and follows a qualitative approach to analyze the findings.
Afgan Kadınlarının 2001 Sonrası Siyasi ve Sosyal Katılımı
▪ Yüksek lisans tezi.